(untitled) (Journal of Dhaka Medical College, 2020)
Neonatal seizures are common in the first month of life and may impair neurodevelopmental outcome. Phenobarbitone (PB) currently represents the anti epileptic drug (AED) of choice, despite related to cognitive impairment in human subjects and limited efficacy. Intravenous levetiracetam is increasingly being used in the neonatal period to treat seizures. Presently, insufficient data about the efficacy and safety of intravenous levetriacetam in neonates, we have structured a randomized control trial with levetiracetam in the initial treatment of acute neonatal seizure. Objective: To find out the efficacy of levtiraracetam for controlling the convulsions in acute neonatal seizures compared to phenobarbitone. Methodology: The study was a randomized control trial. A total of 100 neonates from 0 day to 28 days of age irrespective of sex with clinical presentation of neonatal seizures admitted in the special care baby unit (SCABU) of Dhaka Medical College Hospital were included in the study and were randomly assigned to either levetiracetam or Phenobarbitone group after matching inclusion and exclusion criteria. The outcome variables were seizure control, times taken to be seizure free, and hospital stay. Outcome was evaluated through routine monitoring up to 48 hours and followed up to discharge or death. Result: The study groups were almost similar with respect to their demographic characteristics like age, sex and gestational age. According to maternal obstetric data i.e- antenatal care (ANC), modes of delivery in the both groups were statistically not significant. Seizures status was nonsignificant in both groups. The study demonstrated that controlling the seizure with levetiracetam & Phenobarbitone were 66.0% and 34.0% respectively. Length of the hospital stay was shorter in levetiracetam group. Eventually the phenobarbitone group required more than one drug to control seizures.. But immediate adverse effect was not significant in both groups. Conclusion: The study concluded that levetiracetum significantly control the convulsion in comparison to phenobarbitone as first line antiepileptic drug in the initial treatment of acute neonatal seizures. Both the modalities of treatment were found to have no adverse effect. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 182-189